Developing a "Sponge Catchment Management Plan (SCMP)" framework at the catchment scale: The case of Guiyang, SW China. Issue 1 (13th February 2023) - Qi, Yunfei; Chan, Faith Ka Shun; Feng, Meili; Griffiths, James; Hutchins, Michael; O'Donnell, Emily; Thorne, Colin; Liu, Lingyun; Zhang, Chunguang; Li, Xinan
Abstract: Catchment floods are more challenging due to intensive urbanization and climate change. Enlightened by the Low Impact Development (LID), China initiated the Sponge City Program (SCP) to transform Urban Flood Management (UFM) to be more environmentally friendly in 2013. The China National Government (CNG) has subsidized municipal SCP facilities to enhance urban flood resilience while delivering multiple co‐benefits for urban ecosystems and social well‐being. Recent floods at Schleiden (Germany), Arizona State (USA), and Zhengzhou (China) in 2021 reflected the necessity of Catchment Flood Management (CFM) to cover the whole catchment scale. The SCP, designed to handle small‐scale urban pluvial floods, has brought concerns when facing larger‐scale fluvial floods after the Zhengzhou 2021 flood. Indeed, catchment‐scale Natural Flood Management (NFM) can manage fluvial floods while improving flood adaptations sustainably from upstream to downstream reaches. This research develops a new framework named the Sponge Catchment Management Plan (SCMP), including structural and Nonstructural elements. On the structural side, the SCMP framework integrates NFM with the SCP and Grey Engineering (GE) for reducing the fluvial flood discharge peaks in the whole‐catchment scale. On the nonstructural side, the SCMP encourages collaborative governance, revising technical standards, and improving "bottom‐up" participation. This research used Semi‐Structured Interviews (SSIs) and a Focus Group Approach (FGA) to explore 62 professional and Nonprofessional stakeholders' perspectives on the SCMP framework. Some professional respondents did not know much about the NFM and were worried about the effectiveness of this practice. But most interviewees supported the SCMP pilot work and shared the co‐benefits from the NFM. This case study at the SW China, Guiyang, could be a lesson to encourage other Chinese cities further implement SCP to improve catchment‐scale flood resilience. Abstract : This research develops a new framework named the Sponge Catchment Management Plan (SCMP) that merges Natural Flood Management (NFM) with Sponge City Program (SCP) and Grey Engineering (GE). The Guiyang case also could be a lesson to encourage other cities further implement SCP to improve catchment‐scale flood resilience.